Mapping of the trans population in the Baixada Santista region, Brazil, 2023: a descriptive study - Barbara Iansã de Lima Barroso; Katia Cristina Bassichetto; Denise Leite Vieira; Ísis Gois; Julliana Luiz Rodrigues; Naila Janilde Seabra Santos; Paola Alves de Souza; Angela Tayra; Aline Kumow; Karin Di Monteiro Moreira; Fe Maidel; Maria Amélia de Sousa Mascena Veras; et al. (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To describe the socioeconomic and demographic characteristics of the trans population in the Baixada Santista region, São Paulo state. Methods This was a descriptive study involving adult trans people, selected through convenience sampling in 2023. A quantitative questionnaire was administered and in-depth interviews were conducted, which were analyzed using thematic grouping. Results A total of 237 people were recruited. Of these, 42.2% identified as trans women/travestis and 36.3% as trans men/ transmasculine; 65.4% were aged up to 29 years; 51.1% self-identified as White race/skin color; 52.7% were single; 80.5% had completed at least high school; 32.5% reported no income. Self-perception of transgender identity occurred predominantly between the ages of 10 and 19 (55.7%), with social transition beginning between the ages of 15 and 19 (41.8%). Fourteen in-depth interviews were conducted. Conclusion Socioeconomic factors – education level, employment and income – are central to gender identity. Public actions and policies need to be developed and improved.